Contraintes sur le discours et genre de discours contraint : le commentaire sportif télévisé en direct - Catherine Mathon; Gilles Boyé; Sandra Augendre; Anna Kupść (Discours)
The paper presents an analysis of a specific oral discourse genre, namely live TV sports commentary. The specificity of our work, with respect to previous studies of this genre, is that our proposal takes into account several linguistic aspects simultaneously: prosodic, syntactic and, at a long-term, lexical. Our approach differs also from other studies of discourse genres as not only do we integrate the extra-linguistic constraints into our analysis but also we consider them driving factors for linguistic production of the commentary. Our approach is formalised in terms of Optimality Theory applied to discourse analysis. In order to illustrate our proposal, we provide a detailed annotation of our video corpus of rugby match in terms of game actions and only then do we align them with and analyse linguistic content of the corresponding commentary.